Comparison of the chemical composition of cell-walls of nocardiae with that of other aerobic actinomycetes - Lechevalier, Hubert; Lechevalier, Mary P.; Becker, Benjamin (International Journal of Systematic and Evolutionary Microbiology, 1966)
ABSTRACT Analyses of cell-wall preparations from more than 230 aerobic actinomycetes representing most of the morphological types among those forming well developed mycelia (euactinomycetes) reveal that cell-wall preparations from all actinomycetes contain glucosamine, muramic acid, glutamic acid, and alanine as major constituents. In addition, the broad group of the streptomycetes, including the pathogenic S. somaliensis, contain major amounts of glycine and L-diaminopimelic acid. Preparations from micromonosporae contain glycine and meso-diaminopi-melic acid and those from members of the family Actinoplanaceae contain meso-diami-nopimelic acid with or without glycine. Preparations from strains of Dermatophilus, Thermoactinomyces, Microbispora and nocardiae of the madurae-pelletieri type contain meso-diaminopimelic acid. Preparations from strains of The rmomonospora, Micropolyspora, Pseudonocardia and nocardiae of the farcinica-asteroides type contain meso-diaminopimelic acid, arabinose and galactose. The genus Nocardia is not considered homogeneous with respect to the cell-wall composition of its members. Further studies will undoubtedly show the value of splitting that genus into two groups, but this must await the development of simple and reliable methods for differentiation.